Patients with cerebrotendinous xanthomatosis diagnosed with diverse multisystem involvement - ÖZTÜRK HİŞMİ, BURCU (SPRINGER/PLENUM PUBLISHERS, 2021)
Cerebrotendinous xanthomatosis (CTX) is a lipid storage disease caused by deficiency of sterol 27-hydroxylase enzyme encoded by CYP27A1 gene. This multicenter, cross-sectional descriptive study aimed to document clinical characteristics of CTX patients of different ages, clinical presentations of early-diagnosed patients, and responses to short-term chenodeoxycholic acid (CDCA) treatment. Seven of 11 CTX patients were diagnosed in childhood. Three patients (27%) had neonatal cholestasis, seven (63%) patients had a history of frequent watery defecation started in infantile period, and eight (72.7%) patients had juvenile cataract. Four patients in the adult age group had pyramidal signs and parkinsonism symptoms. The mean Mignarri score at diagnosis was significantly lower in the pediatric patients (267.8 +/- 51.4) than in the adult patients (450.0 +/- 64.0, p = 0.001). No significant difference was determined between pediatric patients and adult patients regarding plasma cholestanol concentration at diagnosis (p = 0.482). The frequency of defecation decreased with treatment in six children, who had diarrhea at admission. Compared to pretreatment values, patients' body weight and standardized body mass index significantly increased at the 12th month of treatment. In conclusion, Mignarri scores are lower in the pediatric patients than in adult patients since the most determinative signs of the CTX disease are not apparent yet in the childhood. The disease is frequently overlooked in routine practice as the disease presents itself with different clinical combinations both in adults and in children. CTX is potentially a treatable disease; thereby, enhanced awareness is critically important for early diagnosis particularly in children.
Keywords: Cerebrotendinous xanthomatosis; Novel mutation; Pediatrics; Cholestanol; CHOLESTASIS; MUTATIONS; GENETICS